VISION AND BLOOD GROUPING: A POSSIBLE LINK. Jamshed Warsi1 , Khaleeq Ur rehman2 , Benazir Mahar3 , Tazeen Shah4 - Jamshed Warsi1 , Khaleeq Ur rehman2 , Benazir Mahar3 , Tazeen Shah4 , Sumia Soomro5 , Waqar Asghar6 , Zunaira Arain7 , Rubina Khalid8 ., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: The ABO blood group was discovered in 1900 century by Austrian, Karl Landsteiner. Since then, the importance of blood typing could not be denied because of its possible association with different physiological and pathological conditions of individuals; hence ABO/Rh blood is linked with various genetic, metabolic, and pathological conditions. OBJECTIVE: After the discovery of ABO blood group, the escalating importance of blood grouping cannot be denied in transfusion/ blood banking, Furthermore, recent research studies revealed that blood group is also associated with many pathologies. The aim of the studies, hence, is to find out the possible link between visual acuity and blood grouping. METHODS: A cross sectional (survey based) work was conducted with the sample size (n) of 424 (male and female). Blood grouping was performed and different charts (Snellen, Tumbling E and Jager) were used to find out the visual acuity. Total 848 eyes were monitored. RESULTS: According to Snellen’s chart the highest percentage of abnormal eyes were found in O blood groups (in male) 44(10.18%) and 79(19.0%) in B blood groups in female. 120(27.78%) males and 199(47.84%) females were Rh+ with abnormal vision. According to Tumbling E chart, the highest percentage of abnormal eyes were found in O blood groups (in male) 50(11.57%) and 80(19.23%) in B blood groups in female. 127(29.40%) males and 206(49.52%) females were Rh+ with abnormal vision. According to Jager chart, the highest percentage of abnormal eyes were found in B blood groups (in male) 27(6.25%) and 37(8.89%) in female. 69(15.97%) males and 96(23.08%) females were Rh+ with abnormal vision. CONCLUSION: abnormal vision (far vision) is apparently more in o blood group in male and B blood group in female and B was associated with near vision in both male and female.